Varstvo avtohtonih narodnih skupnosti v Ustavi Republike Slovenije - Göncz, László (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
The article explores the drafting and adoption of the Constitution of the Republic of Slovenia in terms of protection of the rights of autochthonous national communities at the time of Slovenia's independence, with an emphasis on the Hungarian national community. Once the Constitution was adopted, the umbrella organisation of the Hungarian community noted that the competences of autochthonous national communities in terms of representation at the state level as well as in the fields of the economy, human resources policy, and use of their symbols expanded and financing became more stable, whereas the constitutional status of autochthonous national communities deteriorated as they were no longer listed as entities contributing to the identity of the state. Moreover, the legislature failed to adopt the planned constitutional law or a general law integrating the most relevant constitutional provisions and encouraging a more consistent implementation and monitoring thereof.
Keywords: autochthonous national communities; avtohtone narodne skupnosti; Constitution of the Republic of Slovenia; Constitutional Commission; legal protection; pravno varstvo; Prekmurje Hungarians; prekmurski Madžari; Ustava Republike Slovenije; Ustavna komisija